Integrating Effective Practices Into Co-Teaching: Increasing Outcomes for Students With Disabilities. (March 2020) - Cook, Sara Cothren; McDuffie-Landrum, Kimberly
Co-teaching is the most popular model for supporting students with disabilities in the general education setting. However, the limited research that supports this framework as effective for increasing outcomes for students with disabilities may indicate co-teachers have difficulty providing students with specialized instruction to meet individual learning needs. In this article, co-teachers are provided a model for integrating effective practices strategically within various co-teaching models to increase educational outcomes for students with disabilities.